MODERN IN TEACHING FOREIGN LANGUAGES AT SCHOOL ROLE AND SIGNIFICANCE OF TECHNOLOGIES - Tazabayeva, Oltinoy Ergash qizi (INTERNATIONAL CONFERENCES, 2023)
This article is a new way of foreign languages in the general secondary education system quality teaching system for language learners using modern methods aimed at education.